ANALISIS SWOT DALAM STRATEGI PEMASARAN MINUMAN MOJITHOSS DARI UKM MOJITHOSS - Reifo Prima Alamsyah; Muhammad Anas (Universitas Muhammadiyah Surakarta, 2025)
Mojithoss SME is one of the contemporary beverage businesses using soda as the main ingredient. The main problem in product development is marketing, so marketing strategies can overcome these problems. This research uses SWOT analysis to understand and analyze the internal and external situation at Mojithoss SMEs as a basis for determining marketing strategies. The data obtained from Mojithoss SMEs are processed in such a way as to obtain information about strengths, weaknesses, opportunities, and threats. The results of the study obtained four strategies, namely two SO strategies, two WO strategies, three ST strategies, and two WT strategies. Therefore, after the identification is done, it is recommended that Mojithoss SMEs can implement it appropriately.